AB0928 Fatigue in fibromyalgia reflects overall burden of disease. (15th June 2017) - Antivalle, M; Batticciotto, A; Rigamonti, F; Ditto, MC; Gerardi, MC; Talotta, R; Mutti, A; Sarzi-Puttini, P
Abstract : Background: Fatigue in fibromyalgia is a very common and disabling symptom, being reported by over 75% of patients. However, the relationship between fatigue and the different manifestations of fibromyalgia has not been convincingly elucidated. Objectives: Aim of the our work was to study the relationship between fatigue, pain, and somatic symptoms in fibromyalgia. Methods: 123 patients with fibromyalgia classified according to 2010 criteria were studied, 113 Females and 10 Males, mean age 47.41±11.21 years, mean disease duration 6.83±6.52 years. Fatigue was assessed by FACIT-Fatigue questionnaire (13 items, score 0–52, higher values representing less fatigue), and results were correlated to the number of Tender points (TP), to Widespread Pain Index (WPI), to Symptom severity Scale (SSS), and to Polysymptomatic Distress Scale (PDS) values. Correlations were computed by parametric or non parametric methods as appropriate. Results: Average FACIT-Fatigue score (22.51±10.6) was lower than the 25th percentile of the general population (35), and was not correlated to age or to disease duration (p>0.05). FACIT-Fatigue showed statistically significant inverse correlations with the number of tender points (r = -.303, p=0.001), WPI score (r=-0.329, p<0.001), SSS score (r=-0.651, p<0.001), PSD score (r=-0.522, p<0.001), and with the total number of somatic symptoms (r=-0.594, p<0.000) (Fig. 1, right panel). Furthermore, for each of the 40 somatic symptoms suggested by 2010 criteria, the presence of the symptoms was associated with higher levels of fatigue (Fig 1, left panel). Conclusions: The results of our study confirm that fatigue is a prominent feature of fibromyalgia. Higher levels of fatigue reflect higher levels of widespread pain, and a higher burden of somatic symptoms. Disclosure of Interest: None declared